The Influence of Principal Instructional Leadership and Teacher Work Motivation on Elementary School Teacher's Teaching Performance - Nurisnaeni Nurisnaeni; Munir Munir; Asep Suryana (Papanda Publisher, 2026)
This study aims to analyze the influence of instructional leadership of school principals and teachers' work motivation for the teaching performance of elementary school teachers in Tegalwaru District, Purwakarta Regency. The approach used is quantitative with correlation and multiple regression methods. The study population included 237 teachers from 25 elementary schools, with a sample of 142 teachers determined through proportional random sampling techniques. Data was collected using a five-point Likert scale questionnaire that has been tested for validity and reliability. Data analysis was carried out with the help of SPSS 24 through descriptive statistics, prerequisite tests, correlation tests, determination coefficients, F tests and t tests, as well as the preparation of regression equations. The results showed that instructional leadership had a significant effect on teaching performance with a contribution of 43.6%, work motivation had a significant effect with a contribution of 30%, and simultaneously both explained 47.6% of teacher performance variations. Implication, strengthening instructional leadership and a system of increasing work motivation needs to be a priority for elementary school policies. It is recommended that school principals improve academic supervision, coaching, and professional support, while teachers develop pedagogic competencies and classroom management through continuous development programs. Follow-up research is recommended to include other factors outside the model, such as school culture, parental support, and learning facilities, to explain the remaining variation in performance and enrich the development of teacher performance management models at the primary education level.